.x-med-a. : Experimental media arts. - Bernard, Yves; Kuzmanovic, Maja; Maes, Annemie; nadine (Brussels : [s.n.], 2006)
Maes, Annemie ; Oliver, Julian ; Kusaite, Lina ; Kubota, Akihiro ; Rokeby, David ; RGB~toysband ; Schacher, Jan ; Seymour, Sabine ; Raes, Casey ; Jacobs, Margot ; Viaene, Els ; et al.
Originated from a series of technically, artistically and poetically juicy workshops, organized by four independent technological arts initiatives in Brussels: nadine, okno, FoAM and iMAL
kunstcatalogus